The Effect of Secure Attachment State and Infant Facial Expressions on Childless Adults’ Parental Motivation - Ding, Fangyuan; Zhang, Dajun; Cheng, Gang (Frontiers in Psychology, 2016)
This study examined the association between infant facial expressions and parental motivation as well as the interaction between attachment state and expressions. Two-hundred eighteen childless adults (Mage = 19.22, 118 males, 100 females) were recruited. Participants completed the Chinese version of the State Adult Attachment Measure and the E-prime test, which comprised three components (a) liking, the specific hedonic experience in reaction to laughing, neutral, and crying infant faces; (b) representational responding, actively seeking infant faces with specific expressions; and (c) evoked responding, actively retaining images of three different infant facial expressions. While the first component refers to the “liking” of infants, the second and third components entail the “wanting” of an infant. Random intercepts multilevel models with emotion nested within participants revealed a significant interaction between secure attachment state and emotion on both liking and representational response. A hierarchical regression analysis was conducted to examine the unique contributions of secure attachment state. Findings demonstrated that, after controlling for sex, anxious, and avoidant, secure attachment state positively predicted parental motivations (liking and wanting) in the neutral and crying conditions, but not the laughing condition. These findings demonstrate the significant role of secure attachment state in parental motivation, specifically when infants display uncertain and negative emotions.